The Cheng Beng Tradition in Indonesian Chinese Ethnic Communities: The Psychological Construct of Spirituality, Emotional Well-Being, and Social Identity - Ivory; Marselius Sampe Tondok (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
“Cheng Beng” is an annual tradition carried out by ethnic Chinese people in Indonesia to honor their ancestors by visiting cemeteries to clean the graves and make offerings. This research explores the psychological constructs related to the Cheng Beng ceremony using a qualitative method with a narrative literature study approach. The data were collected through interviews and literature review, with subjects selected using purposive sampling. Three themes emerged from the interviews: the implementation of the Cheng Beng tradition, its meaning, and changes in its implementation of Cheng Beng. The literature review revealed the themes of respecting ancestors, strengthening family bonds, and enhancing relationships with other ethnic groups. The psychological constructs explored in this research are spirituality, emotional well-being, and social identity. Participating in the Cheng Beng tradition fosters a spiritual connection with ancestors, enhances emotional well-being by helping individuals cope with feelings of loss, connects to the family who have died. Participating in this ceremony strengthens one’s connection to Chinese culture and family history, which in turn strengthens their social identity as members of the Chinese community.